ESSA1 embryonic stem like cells from gilthead seabream: a new tool to study mesenchymal cell lineage differentiation in fish - Parameswaran, V. (2014)
Embryonic stem (ES) cells are a promising tool for generation of transgenic animals and an ideal experimental model for in vitro studies of embryonic cell development, differentiation and gene manipulation. Here we report the development and initial characterization of a pluripotent embryonic stem like cell line, designated as ESSA1, derived from blastula stage embryos of the gilthead seabream (Sparus aurata, L). ESSA1 cells are cultured in Leibovitz’s L-15 medium supplemented with 5% fetal bovine serum and, unlike other ES cells, without a feeder layer. They have a round or polygonal morphology, grow exponentially in culture and form dense colonies. ESSA1 cells also exhibit intense alkaline phosphatase activity, normal karyotype and are positive for stage-specific embryonic antigen-1 (SSEA1) and octamer-binding transcription factor 4 (Oct4) markers for up to 30 passages. Upon treatment with all-trans retinoic acid, ESSA1 cells differentiate into neuron-like, oligodendritic, myocyte and melanocyte cells; they can also form embryoid bodies when seeded in bacteriological plates, a characteristic usually associated with pluripotency. The capacity of ESSA1 cells to differentiate into osteoblastic, chondroblastic or osteoclastic cell lineages and to produce a mineralized extracellular matrix in vitro was demonstrated through histochemical techniques and further confirmed by immunocytochemistry using lineage-specific markers. Furthermore, ESSA1 cells can be used to produce chimera, where they contribute to the development of a variety of tissues including the trunk and gut of zebrafish embryos and fry. Thus, ESSA1 cells represent a promising model for investigating bonelineage cell differentiation in fish and also highlight the potential of piscine stem cell research.